Pekerja Migran Indonesia dalam Perspektif Ekonomi dan Hukum Internasional - Nur Syamsiah; Radimin (Jurnal Global Futuristik, 2025)
This study aims to analyze Indonesian migrant workers from an international economic and legal perspective. This study uses a normative legal research method with a statute approach and a conceptual approach. The data used are secondary data obtained through literature studies, including laws and regulations and scientific journals relevant to migrant workers. The results of the study indicate that Indonesian migrant workers have an impact on the economic and international legal fields. In the economic field, the presence of Indonesian migrant workers can improve the economy, reduce unemployment rates in their countries of origin, and provide skills for Indonesian migrant workers. However, on the other hand, the negative impacts create dependence on work as Indonesian migrant workers. Meanwhile, from an international legal perspective, Indonesian migrant workers are objects of international law. There are several conventions that regulate Indonesian migrant workers. The aim is to provide protection to Indonesian migrant workers working abroad.